2001
DOI: 10.1542/peds.108.5.e87
|View full text |Cite
|
Sign up to set email alerts
|

Acute Helicobacter pylori Infection Is Followed by an Increase in Diarrheal Disease Among Peruvian Children

Abstract: ABSTRACT. Background. Cohort and case-crossover studies were conducted to evaluate whether new Helicobacter pylori infections are followed by increased diarrhea.Methods. Participants were 6-month-old to 12-yearold shantytown residents living near Lima, Peru. Baseline data were collected from community households. Health interviews were completed daily, and sera, drawn every 4 months, were tested for H pylori immunoglobulin G. Diarrhea rates among newly H pylori-infected (seroconverting) children were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
3
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 59 publications
2
53
3
1
Order By: Relevance
“…This effect was greater in the two months after infection. 27 In Thailand, no difference in the incidence of diarrheal disease according to the H. pylori infection was found among children less than five years of age, either in those who acquired the infection during the study in contrast to the prevalent cases or among these and children who remained negative during the follow-up. 26 In the Colombian cohort study, a positive association was found between the H. pylori -infected children and the days absent from nursery school because of respiratory infections.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…This effect was greater in the two months after infection. 27 In Thailand, no difference in the incidence of diarrheal disease according to the H. pylori infection was found among children less than five years of age, either in those who acquired the infection during the study in contrast to the prevalent cases or among these and children who remained negative during the follow-up. 26 In the Colombian cohort study, a positive association was found between the H. pylori -infected children and the days absent from nursery school because of respiratory infections.…”
Section: Discussionmentioning
confidence: 85%
“…However, results from studies on the incidence of diarrheic episodes in infected and noninfected children are not consistent. 26,27 Passaro and others in a retrospective cohort found that children seropositive for H. pylori had more and lengthier episodes of diarrhea the year after the acquisition of the infection than children who were not infected. This effect was greater in the two months after infection.…”
Section: Discussionmentioning
confidence: 98%
“…For example, studies using different inbred mouse lines have shown that the severity of inflammation, and thus potentially the risk of overt disease, that a given H. pylori strain can elicit is affected by the host genotype (17,18). Indeed, the historic importance of cholera and other diarrheal diseases as a major cause of death in the Indian subcontinent and the importance of H. pylori infection in increasing susceptibility to enteric pathogens (10,33,40) might have helped select for human genotypes that result in decreased virulence during chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study focused on H. pylori strains from residents of Las Pampas de San Juan de Miraflores (PSJM), a periurban shantytown of 40,000 persons of low income (Յ$1,500 per family per year, on average) in Lima, Peru, that is representative of many developing-country societies. The health of the residents of PJSM has been under surveillance for more than 20 years by physicians and health care and social workers of the Peruvian nongovernmental organization Proyectos en Informtica, Salud, Medicina y Agricultura (PRISMA; http://www .prisma.org.pe/nwWeb/Portal/) (23,29,30,37). Most residents of PJSM become chronically infected with H. pylori in early childhood (30), as is typical in developing countries worldwide (8,19).…”
Section: Methodsmentioning
confidence: 99%
“…Such chronic H. pylori infections constitute major risk factors for duodenal and gastric ulcers and for gastric cancer, one of the most frequently lethal malignancies (3,13,33). Especially among the poor in developing countries, H. pylori infection also increases susceptibility to other food-and waterborne pathogens and contributes to iron deficiency anemia and malnutrition (10,37,46). This said, most infections seem to be benign; and some, it has been argued, can even be beneficial (7), although the latter view is controversial (25).…”
mentioning
confidence: 99%